Tren Ngopi Sebagai Gaya Hidup Di Kalangan Generasi Z Di Kota Denpasar Barat - Br Sembiring, Hebriene Amanda; Kamajaya, Gede; Aditya, I Gst. Ngr. Agung Krisna (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
ABSTRACT This study aims to analyze how the coffee trend has developed into a lifestyle among Generation Z in West Denpasar City, especially in coffee shops in the Simpang Enam Teuku Umar area. Generation Z is known as a generation that is familiar with technology, active on social media, and makes consumption a part of expressing self-identity. The activity of drinking coffee is no longer just enjoying coffee, but has transformed into a status symbol, social space, and a medium for self-actualization. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. Informants consist of Gen Z visitors, baristas, and individuals who do not do coffee drinking activities in coffee shops. David Chaney's lifestyle theory and the AIO (Activity, Interest, Opinion) approach are used to analyze consumption behavior and social motives behind the coffee trend. The results of the study show that coffee activities have negotiated lifestyles in the daily lives of Gen Z and reflect five forms of lifestyle according to David Chaney: 1. Lifestyle and appearance industry, 2. Lifestyle advertising, 3. Plagiarized lifestyle journalism as imitation, 4. Independent 8lifestyle as self-image, and 5. Hedonistic lifestyle. Coffee shops are chosen not only because of the product but also because of the image, comfort, and social values offered. Keywords: Coffee, Lifestyle, Generation